Алгоритм та програми для мінімізації температурних похибок волоконно-оптичних гіроскопів, встановлених на штучних супутниках землі - Бреславський, Дмитро Васильович; Пащенко, Сергій Олександрович; Успенський, Валерій Борисович (НТУ "ХПІ", 2018)
Надано опис розроблених алгоритмів та програм, що застосовуються для калібрування волоконно-оптичних гіроскопів, які працюють в умовах теплозмін при русі літального апарату навколоземною орбітою. Наведено математичну постановку задачі нестаціонарної теплопровідності, яку розв'язано комбінацією методу скінченних елементів та різницевого методу інтегрування за часом. За допомогою розробленого програмного засобу визначено розподіл температур у корпусі супутника та безпосередньо у волоконно-оптичному гіроскопі у вигляді часової залежності. Знайдений розподіл дає змогу, по-перше, обґрунтувати вимоги до наземного калібрування гіроскопів для побудови відповідних компенсуючих моделей; по-друге, використовувати такі моделі в умовах невизначеності поточної температури гіроскопу за причин, скажімо, відмови термодатчику. Таким чином здійснюється мінімізація температурної похибки приладів під час їх функціонування у складі бортових систем орієнтації та навігації та підвищується їхня відмовостійкість.

The description of the developed algorithms and programs, which are used for calibration of fiber-optic gyroscopes working in the conditions of heat varying during spacecraft’s motion in circumterrestrial orbit, is discussed. The mathematical statement for problem of non-stationary heat conduction for the satellite frame and on-board devices is presented.The method of numerical solution is based on the combination of Finite Element Method for boundary value problem and finite difference time integration method for initial one. The developed approach which allows use the parallel calculations in heat problems, is described. The information about developed software is presented by description of main functions written in C++ language. The temperature distribution in dependence on time in the satellite frame and directly in fiber-optic gyroscope’s shell is found by use of developed software. Found distribution makes an opportunity at first to justify demands for ground calibration of gyroscopes for obtaining the compensation models. Secondly, the use of similar models in the conditions of uncertain value of gyroscope’s temperature, which can be, for example, in the case of heat-sensing device’s failure, can be done. The mathematical model of fiber-optic gyroscope snap data is discussed. The hypothesis of the linear dependence of the drift motion from temperature is suggested. The description of calibration algorithm for temperature model of fiber-optic gyroscope is presented. It was concluded that the main influence on the errors of fiber-optic gyroscope measurements is caused by temperature gradient and influence of absolute temperature is not so significant. Thereby, the minimization of temperature error of devices, which are affiliated in orientation and navigation on-board systems, can be performed as well as fail safety of such systems can be increased by use of the presented methods and algorithms.
Algorithm and software for minimization of temperature errors of fiberoptic gyroscopes, mounted on artificial earth satellites
Keywords: алгоритм; програма; нестаціонарна теплопровідність; штучний супутник Землі; волоконно-оптичний гіроскоп; температурна модель похибок; калібрування; algorithm; program; non-stationary heat conduction; artificial Earth satellite; fiber-optic gyroscope; temperature model of errors; calibration